Evaluating Public Website Performance: Content Analyses on Malang City Government Website - Sajida Sajida; Laela Tul Husna; Karina Widya Rahayu; Indah Ayu Suryawati (Journal of Governance, 2023)
This study evaluates the performance of public websites in Malang City, a heavily digitizing government. Using content analysis, we determine the extent to which the availability of public information has been met and what records still need to be corrected by the Malang city government. This study examines five criteria: information quality, usability, privacy and security, interaction, and accessibility. As a result, the Malangkota. go. id website met the evaluation criteria for general public information availability. However, the government still needs improvement in terms of security and citizen-centered values. Thus, in the future, this research can be used as a basis for policy considerations by the Malang City government to improve the performance of its public services through the provision of good public information.